Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan Pelanggan Pada Salon IC Beauty Bandung - Yuli Yanti Indah Sari; Makmur (Global Leadership Organizational Research in Management, 2024)
This research aims to determine the effect of service quality and trust on customer satisfaction at IC Beauty Salon. To be able to gain an advantage in the competition for service quality, a company must meet customer satisfaction by implementing a strategy for the services offered. Customer trust is influenced positively and significantly by aspects of service quality and trust. Competition in the beauty industry is currently quite fierce along with the increasing interest of women and men in beautifying themselves. With this trust in consumers, IC Beauty now has 1 center and 1 central branch located on Jl. Surya Sumantri 106 branch is located on Jl. Ciumbeluit No. 49 Bandung . The quantitative research method used a sample of 61 respondents. The main data source used is primary data obtained from questionnaires that have been distributed to IC Beauty customers.